2020
DOI: 10.4081/jbr.2020.8949
|View full text |Cite
|
Sign up to set email alerts
|

The Analysis of the Differences between the Influence of Herbal Mouthwashes and the Chlorhexidine Mouthwash on the Physical Characteristics of Orthodontic Acrylic Resin

Abstract: The present study, intended to compare the effects of immersion in herbal mouthwashes and the Chlorhexidine mouthwash on orthodontic acrylic resin, specifically with regard to alterations in its hardness, roughness and color. Seventy-two specimens of Orthodontic self-cured acrylic resin were used for the experiments. After preparation, specimens were placed in three types of mouthwash including Chlorhexidine 0.2 % (CHX), Persica and Matrica. The changes in microhardness (ΔKNH), Surface roughness (ΔRa) and colo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…Possibly due to water absorption by the acrylic resin causing subsequent leach out of plasticizers and breakage of resin material. 34 These results agreed with the findings of some authors 5,34,26 who stated that CDCs increase the surface roughness of DBM resins by hygroscopic expansion, polymer degradation, immersion in warm solutions, as well as by the increase of pH of immersing solution.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Possibly due to water absorption by the acrylic resin causing subsequent leach out of plasticizers and breakage of resin material. 34 These results agreed with the findings of some authors 5,34,26 who stated that CDCs increase the surface roughness of DBM resins by hygroscopic expansion, polymer degradation, immersion in warm solutions, as well as by the increase of pH of immersing solution.…”
Section: Discussionsupporting
confidence: 89%
“…Previously, it was found that ethanol and water act as plasticizers that soften the DBM through penetration into the interpolymeric spaces causing separation of the polymer chains and plastic deformation. 26 These findings are in accordance with Degirmenci et al 7 who reported that Corega and CHX produced notable changes in the surface roughness of resin DBM compared to DW solution.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…A combination of inadequate or excessive antibiotic use and difficulties in accessing topical agents with efficacy against biofilms have led to an increase in antibiotic resistance. Dental biofilms can be controlled with chlorhexidine (CHX), a cationic broad-spectrum antibacterial [82]. An important component of this effectiveness is substantivity, a property that binds the molecule to tissues and exerts antibacterial activity for over 12 h after application.…”
Section: Pdt In Preimplantitismentioning
confidence: 99%
“…Learning details of materials are very important for customizing them for specific applications, and such issues are currently the targets of several studies using various aspects and methods [37][38][39][40]. Among such efforts, the herbs have been found very interesting to be explored in addition to the exploration of other types of drugs and biomaterials modifications [41][42][43]. To this aim, the current review work was systematically focused on effects of herbal sativa on hypertension to provide more insights into the issues of metabolic syndrome.…”
Section: Introductionmentioning
confidence: 99%